Public Transport Performance Based on the Potential Demand and Service Area (Case Study : Jakarta Public Transport) - Muchammad Zaenal Muttaqin; Yori Herwangi; Cahyono Susetyo; Tri Sefrus; Muhammad Subair (Daengku: Journal of Humanities and Social Sciences Innovation, 2021)
The effectiveness and efficiency of public transport should be a priority for transportation in developing cities. Despite the efforts from the government to improve public transportation, in Jakarta City, Indonesia, there is still 9.93% increase of private vehicles annually per year. In detail, contributor for increasing vehicles in Jakarta is motorcycles with an average annual increase of 10.54% every year, followed by an increase in the percentage of passenger cars by 8.75%. In contrast, the number of public transportation increased only by 1.74%. This research did the evaluation for public transport service in Jakarta by availability and accessibility for them. Neighborhood analysis and Proximity analysis used in this research. The results of the research showed that major problems in public transportations in Jakarta City are the coverage area of the service, route connectivity, and its accessibility for public facilities. There are only 7.78% for coverage area by flexible bus stop service with average walking distance by 300 m. Thus, there are some areas that are not passed by public transport routes, for about 18.5 million people live in blank spot area.